16S rRNA‐functionalized multi‐HCR concatemers in a signal amplification nanostructure for visual detection of Salmonella. (11th June 2020) - Qu, Guijuan; Sun, Xiuwei; Ying, Na; Bu, Shengjun; Li, Zhongyi; Hao, Zhuo; Wu, Haibo; Wan, Jiayu
Abstract: To prevent foodborne diseases and minimize their impacts, it is extremely important to develop a cost‐effective and efficient bacterial detection assay for diagnostics, particularly in resource‐poor settings. In this study, 16S rRNA from foodborne Salmonella was coupled with multiple HCR (hybridization chain reaction) concatemers and functionalized in a signal structure for lateral flow nucleic acid biosensor (LFNAB) detection. The 16S rRNA was incubated with two specific capture probes and multiple helper probes carrying the same initiator, to unwind its secondary structure and form an "initiators‐on‐a‐string" complex. Through use of the initiators, each target 16S rRNA yielded multiple HCR concatemers tethered to numerous biotins, and numerous streptavidin‐labeled gold nanoparticles were introduced on the LFNAB. The limit of detection was 53.65 CFU/mL for Salmonella . Notably, this method has high specificity and applicability for the detection of Salmonella in food and water samples.